2013
DOI: 10.1007/s13312-013-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth parameters in children with dyspepsia symptoms and Helicobacter pylori infection

Abstract: Controversy exists about relationship of H. pylori infection and somatic growth retardation of children. The aim of this study was to evaluate the relationship between H. pylori infection and growth parameters in children. 113 children with dyspepsia (4-18 years) were enrolled. C13 urea breath test was performed for determination of H.pylori infection. Height, weight, body mass index (BMI) and standard deviation score (SDS) was calculated and growth parameters were compared between two groups of H.pylori posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 7 publications
0
19
0
2
Order By: Relevance
“…12 Another cross-sectional study among children from a low-income country reported a significantly higher number of H. pylori-infected children than non-infected children falling below the 5 th percentile of height-for-age. 31 In contrast with these findings, no association between height and H. pylori infection was reported in studies of children from Alaska, 32 Australia, 33 Iran, 34 and Guatemala. 35 These inconsistent findings could be due to variations in age, outcome ascertainment, and differences in the method used for the assessment of H. pylori status.…”
Section: Discussionmentioning
confidence: 79%
“…12 Another cross-sectional study among children from a low-income country reported a significantly higher number of H. pylori-infected children than non-infected children falling below the 5 th percentile of height-for-age. 31 In contrast with these findings, no association between height and H. pylori infection was reported in studies of children from Alaska, 32 Australia, 33 Iran, 34 and Guatemala. 35 These inconsistent findings could be due to variations in age, outcome ascertainment, and differences in the method used for the assessment of H. pylori status.…”
Section: Discussionmentioning
confidence: 79%
“…This association became nonsignificant after controlling for socioeconomic variables, and no differences were found between the groups in the average weight, body mass index (BMI), and BMI z score (40). Similarly, other studies found no differences between H pylori-infected and -uninfected children in average weight (38), BMI, weight-for-age z score (WAZ) (11), weight for age percentile (25,35) or WHZ (11)(12)(13)15,31,36). In the Czech Republic, children who had evidence of H pylori infection had a significantly lower mean BMI than did uninfected ones, independent of socioeconomic factors (23); however, a recent study from the same country showed null results with weight and BMI (24).…”
Section: H Pylori Infection and Body Weightmentioning
confidence: 90%
“…Six papers reported UBT/stool results on H. pylori infection in symptomatic children (symptoms include: gastrointestinal symptoms, dyspepsia/dyspeptic symptoms, chronic abdominal pain, recurrent abdominal pain, upper abdominal pain or suspicion of peptic diseases; code 4 from Figure ) (Figure [references: ]). The random‐effects regression model shows 42% H. pylori prevalence (95% CI: 25%‐59%).…”
Section: Resultsmentioning
confidence: 99%